Triplex viability PCR for simultaneous quantification of Lactobacillus acidophilus, Streptococcus thermophilus, and Bifidobacterium bifidum in live microbial formulations - Del Pio, Luca; Catone, Stefania; Pisani, Giulio; Franciosa, Giovanna (Frontiers in Microbiology, 2026)
Live microbial formulations frequently contain strains of Lactobacillus acidophilus, Streptococcus thermophilus and Bifidobacterium bifidum in combination. Accurate determination of microbial identity and viable counts is essential for ensuring product functionality and to meet regulatory requirements. Here, a triplex propidium monoazide (PMA) qPCR assay, referred to as triplex viability PCR (vPCR), was developed for the identification, quantification, and viability assessment of these key microbial species. Primers and TaqMan probes were first evaluated for compatibility and specificity. Heat treatments were applied to inactivate microbial cells, and optimal PMA concentrations were determined to effectively discriminate between live and dead microbial cells. Amplification conditions were optimized to enable the simultaneous generation of standard curves for all three target species using their respective primer/probe sets. The triplex vPCR assay produced three distinct amplification signals and the corresponding standard curves demonstrated good assay reproducibility, with R2 values greater than 0.98 and reaction efficiencies between 90 and 110%. The optimized protocol allowed accurate viable quantification of L. acidophilus and B. bifidum over a range of approximately 10 to 107 CFU/mL, and of S. thermophilus over 30 to 3×107 CFU/ml. Application of the protocol to a commercial multi-species live microbial formulation provided consistent viable quantification for all three species. Plate counts were generally lower than both triplex qPCR and triplex vPCR measurements, while triplex vPCR values were lower than triplex qPCR, reflecting selective exclusion of DNA from dead cells. By combining multiplexing, high-efficiency reagents, and a PMA pretreatment that selectively prevents amplification from non-viable cells, this triplex vPCR method overcomes the limitations of culture-dependents techniques and standard qPCR, improves analytical throughput, reduces variability, ensuring accurate quantification of viable microorganisms.